Analisis Bibliometrik terhadap Perkembangan Riset Internasional mengenai Implementasi Montessori dalam Pendidikan Inklusi - Rita Anisaturrizqi; Prima Cristi Crismono; Anis Rofi Hidayah (Early Childhood Journal, 2025)
Abstract In an era of increasingly inclusive and future-oriented education, research on the development of Montessori approaches and inclusive education has become highly relevant and important. This research aims to analyze the development of research on Montessori education and inclusive education globally, including the integration of special needs such as dementia care. The method used is a descriptive quantitative approach with bibliometric analysis through data from the Scopus database, using related keywords such as "Montessori education" and "inclusive education." Data were collected from relevant articles and then analyzed to identify publication trends, geographic distribution, institutional contributions, as well as the relationships between concepts through network visualization and heat maps. The research results indicate that the United States dominates in publications and institutional contributions, followed by European countries and Australia. The publication trend shows a significant increase year on year, with a growing focus on inclusion and dementia care issues in the Montessori context. Network visualizations display the complex relationships among innovative educational concepts and various methodological approaches. These findings emphasize the importance of strengthening international collaboration and developing educational policies that support inclusive Montessori approaches, as well as demonstrating that developments in this research play a crucial role in expanding the adoption and innovation of global education that is responsive to the diverse needs of learners.